Wpływ poziomu gospodarczego na nierówności płac w Polsce - krzywa Kuznetsa - Kumor, Paweł (Annales. Etyka w Życiu Gospodarczym, 2009)
In the article we made an attempt to estimate the impact of structural economic changes on inequalities of earnings in Poland. The processes of structural changes were represented by GDP per one employee. Inequalities of earnings were measured with Lorenz coefficient. Additionally we used a variable, representing the health human capital  infant death rate in a thousand living births. On the basis of 19802006 sample we proved Kuznets’ hypothesis about the parabolic impact of GDP per one employee on inequalities of earnings. In the studied period economy was found on the left arm of the parabola. The increase of GDP level per one employee favoured the increase of inequalities. Our estimates resulted in the fact that inequalities of earnings can maximally increase by about 1.4 percentage point. We think that according to Kuznets’ hypothesis inequalities will start to fall when GDP per one employee exceeds 103,000 PLN worth. The studies confirm the negative impact of the human capital measure  infant birth rate on inequalities.We hope that this article enables to better understand market mechanisms influencing inequalities of earnings.